The neutrophil antigen 3a/b polymorphism in SLC44A2 unexpectedly encodes the Csa/Csb red cell antigens - Duval, Romain; Soudry, Alissa; De Oliveira Rios, Jonathan; Linguet, Sarah Liane; Taillepierre, Miguel; Matesic, Graziella; Raneri, Alexandre; Laiguillon, Guy; Le Toriellec, Emilie; Gautier, Emilie-Fleur; Vainqueur, Damien; Babinet, Jérôme; et al. (Blood, 2025)
•The HNA-3a/b polymorphism underlies the genetic basis of the Csa/Csb red cell antigens.•Anti-Csa and anti-HNA-3a recognize different epitopes on the SLC44A2 protein. [Display omitted] The Csa blood group antigen was identified >50 years ago, but its genetic basis has yet to be elucidated. All our recent genomic investigation has failed to resolve the genetic basis of this enigmatic antigen. By investigating the association of the human neutrophil antigen (HNA)-3a/b polymorphism (rs2288904-G/A) in SLC44A2 with clinical features of sickle cell disease, we incidentally discovered that rare subjects with the homozygous HNA-3b/b genotype also carry the uncommon Cs(a–) phenotype. We genotyped this single-nucleotide polymorphism in a cohort of 25 Cs(a–) subjects and found that all of them showed an HNA-3b/b genotype. This result suggests that the high-prevalence allele with rs2288904 (HNA-3a; 455G) encoding Arg152 encodes the high-prevalence Csa. Accordingly, anti-Csa does not react with solute carrier (SLC)44A2null red blood cells (RBCs), SLC44A2 knockout K562 cells, and K562 cells expressing HNA-3b, confirming that the Csa and Csb antigens are carried on this protein. Furthermore, mass spectrometry analysis of SLC44A2 from neutrophils and RBCs, along with serological investigation, showed that, despite HNA-3a and Csa having the same genetic basis, anti–HNA-3a and anti-Csa recognize different epitopes on the SLC44A2 protein. Overall, our data resolve the genetic bases of the Cs(a–) and Cs(b–) blood phenotypes, with new insights on the anti–HNA-3a specificity.